SWCNT‐MoS2‐SWCNT Vertical Point Heterostructures. Issue 7 (6th December 2016) - Zhang, Jin; Wei, Yang; Yao, Fengrui; Li, Dongqi; Ma, He; Lei, Peng; Fang, Hehai; Xiao, Xiaoyang; Lu, Zhixing; Yang, Juehan; Li, Jingbo; Jiao, Liying; et al.
Abstract : A vertical point heterostructure (VPH) is constructed by sandwiching a two‐dimensional (2D) MoS2 flake with two cross‐stacked metallic single‐walled carbon nanotubes. It can be used as a field‐effect transistor with high on/off ratio and a light detector with high spatial resolution. Moreover, the hybrid 1D–2D–1D VPHs open up new possibilities for nanoelectronics and nano‐optoelectronics.